Tradisi Upacara Adat Mandi Kasai (Kajian Etnografi di Kota Lubuklinggau) - Isbandiyah Isbandiyah; Supriyanto Supriyanto (SINDANG: Jurnal Pendidikan Sejarah dan Kajian Sejarah, 2023)
This reseach uses qualitative method with etnography approach is to: (1) describing tradition of mandi kasai ceremony in Lubuklinggau; (2) describing the use of mandi kasai ceremony in Lubuklinggau; (3) constructing citizen perception about mandi kasai in Lubuklinggau. The results showed that is tradition of mandi kasai ceremony is a part of wedding ceremony for citizen in Lubuklinggau. The ceremony is held by bridegroom after doing ceremony by using tool and infrastructure of ceremony. Tradition of mandi kasai ceremony two meanings: (a) bridegroom go out from singgle status. After merried, that have to know that they must obey the rule as spouse; (b) before merried, the bridegroom is clean and holy. Citizen in Lubuklinggau have different perception about mandi kasai ceremony, some of them support this tradition, but some of them dare it, all of them have strong reason that can be accepted.